Computers in Cardiology 1999. Vol.26 (Cat. No.99CH37004)
DOI: 10.1109/cic.1999.826031
|View full text |Cite
|
Sign up to set email alerts
|

Atrial rate variations in atrioventricular block patients: influences of ventricular rate and atrioventricular delay

Abstract: Atrial rate variations (AR v) of nine atrioventricular (AV) block patients loaded with VDD pacemakers were analyzed with pacemaker-of mode, programmed at different fuced ventricular pacing rates (60, 90, 120 bpm) and with different AV delays in VDD pacing (80, 120, 160, 200 ms) to stu& the infuences of ventricular rate and AV delay. ARV were measured by PP intervals on the atrial electrocardiogram (ECG) that was non-invasive& recordedfrom an esophageal lead In results, all ARV measures had no signiJicant dtfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…But in our previous study under an AV disassociation condition, e.g. fixed-rate ventricular pacing, the atrial rate variability (ARV), was measured and showed a pattern in which the main frequency components varied with the ventricular rates [1]. Some studies was reported that ventricular rate and AV-delay have marked influences on ARV [2,3] Moreover, some evidences have shown that beat-to-beat blood pressure (BP) variation (BPV) may play a role for this phenomenon [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…But in our previous study under an AV disassociation condition, e.g. fixed-rate ventricular pacing, the atrial rate variability (ARV), was measured and showed a pattern in which the main frequency components varied with the ventricular rates [1]. Some studies was reported that ventricular rate and AV-delay have marked influences on ARV [2,3] Moreover, some evidences have shown that beat-to-beat blood pressure (BP) variation (BPV) may play a role for this phenomenon [4,5].…”
Section: Introductionmentioning
confidence: 99%